Perbandingan sitotoksisitas Endomethasone, AH Plus, dan Apexit Plus terhadap sel fibroblas dengan teknik root dipping - Christine A. Rovani; Kamizar Kamizar; Munyati Usman (Journal of Dentomaxillofacial Science, 2008)
The purpose of this study was to evaluate the lowest cytotoxicity of three endodonticsealers, Apexit Plus, AH Plus and Endomethasone that can be used safely. The crownof 30 intact lower premolars were removed at cementodentinal juntion and the teethwere prepared with crown down technique with # 20 initial file and # 30 masterapical file. After sterilization, the 30 teeth were randomly divided into three groupsand filled with gutta percha using laterally condensation technique and Apexit Plus,AH Plus, and Endomethasone as sealers. Apex of the roots was dipped 1.5 mm intoculture medium for 24 hours in incubator (root dipping technique). The mediumcontact was transformed into confluent chicken fibroblast. Cytotoxicity ofEndomethasone, AH Plus, and Apexit Plus were measured with hemocytometer assay.The results showed that percentage survived cells of Apexit Plus was 68%,Endomethasone 66.42%, and AH Plus 64%. The amount of exist cells were ApexitPlus>Endomethasone>AH Plus. There was no significant difference of cytotoxicityamong the sealers (P>0.05). The conclusion was the amount of exist cells were morethan 50% which means that the three root canal sealers were not toxic.